Physical and social health needs of postoperative bariatric surgery patients: a focus group - Angela C. Glauser; Robin L. Marcus; Larissa A. McGarrity; Anne Thackeray; Eric T. Volckmann; Alexandra L. Terrill (Discover Social Science and Health)
Abstract Purpose This qualitative study explored the health needs of patients after undergoing bariatric surgery. The study specifically aimed to describe the unique physical, emotional, and social challenges patients face following surgery in order to inform the development of future obesity treatment programs. Methods A 90-min focus group was conducted using a semi-structured interview guide. Bariatric surgery patients were enrolled using purposive sampling. The mean number of months since surgery was 20.2 (SD 10.8). The mean age of participants was 53.3 (SD 9.8) years. The focus group was both audio and video recorded, transcribed, and analyzed using topic and analytical coding. Results Three main themes emerged revealing postoperative needs for (1) assistance with physical changes and reduced barriers to exercise, (2) reinforcement for healthy eating behaviors, and (3) emotional support from peers, family, and community. Conclusions Findings suggest that rehabilitation following bariatric surgery is complex in nature and patients may benefit from both pre- and post-surgery programs that address their unique needs. Weight maintenance and sustaining healthy behavior change post-surgery requires ongoing personal and professional assistance. Interventions should emphasize healthy eating practices, include practical exercise suggestions, and offer social and emotional support.